2008
DOI: 10.1007/s11104-008-9856-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil moisture content on the deformation behaviour of root-reinforced soils subjected to shear

Abstract: This paper presents an experimental study on how soil moisture content affects the deformation behaviour within root-reinforced soils subjected to shear. In-situ shear tests were carried out in this research. The plant used in the shear tests was Prickly Sesban (Sesbania cannabina Merr.). The shear deformation within the root-reinforced soil after shear was measured. The effect of soil moisture content and the root area ratio on the development of the shear zone was investigated. The experimental results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Various studies have been reported to quantify soil moisture/suction under drying (i.e., ET) and wetting (i.e., rainfall or ponding) events in soil vegetated with non-crop species (Simon and Collison, 2002;Smethurst et al, 2006;Fan and Su, 2009;Pollen-Bankhead and Simon, 2010;Smethurst et al, 2012;Ghestem et al, 2014;Veylon, 2015;Leung et al, 2015a, b). In most of these studies, a mix of species was used, making it very hard (if not impossible) to identify the root characteristics of those species and, more importantly, to understand their correlation with suction.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been reported to quantify soil moisture/suction under drying (i.e., ET) and wetting (i.e., rainfall or ponding) events in soil vegetated with non-crop species (Simon and Collison, 2002;Smethurst et al, 2006;Fan and Su, 2009;Pollen-Bankhead and Simon, 2010;Smethurst et al, 2012;Ghestem et al, 2014;Veylon, 2015;Leung et al, 2015a, b). In most of these studies, a mix of species was used, making it very hard (if not impossible) to identify the root characteristics of those species and, more importantly, to understand their correlation with suction.…”
Section: Introductionmentioning
confidence: 99%
“…All data were analysed qualitatively using a combination of maps and plots of summary statistics. Maps were generated within ArcGIS (ESRI 2006) and data were exported and statistical modelling was carried out using the statistical package R (2006). Data were analysed by analysis of variance (ANOVA) or its multivariate counterpart (MANOVA), where appropriate.…”
Section: Data Processingmentioning
confidence: 99%
“…Using the corresponding predicted subsidence contours associated with these points, a series of polygons (2007) corresponding with these zones were created within Arc-GIS (ESRI 2006). Using the spatial join function of Arc-GIS (ESRI 2006), the points within each zone (both block scale and regional scale) were identified.…”
Section: Creating Lms Zones For Impact Assessmentmentioning
confidence: 99%
See 2 more Smart Citations